Sugar Rush / Nur Syafiqah Kaharuddin - Kaharuddin, Nur Syafiqah (2021)
Sugar Rush is an online business founded as of 17 April 2021 to sell sweet dessert to bring happiness to the people that consume it. 1. Product The product that is served by Sugar Rush is Crimebite Cookies which is handmade chocolate cookies that use high quality ingredient to meet customer satisfaction. 2. Market Our target customers include children, student and people that love chocolate. Sugar Rush is a pre-revenue business but has the ability to attract customer. Based on what have been planned, this business will be able to capture at least 25 percent of this market over the next 2 years. 3. Competition Our competition is consisted of Yeen Cookies and Lokal Munchies. Sugar Rush’ competitive advantage lies in its unique product quality and great promotion that build traction of this company. 4. Management Nur Syafiqah Kaharuddin, founder of Sugar Rush is suitable for this opportunity as she has an excellent knowledge on business and able to handle it well. Nur Zafirah Zulkarnain, Co-founder of Sugar Rush that are graduated from program Bachelor of Business Management (Hons) Entrepreneurship and have 3 years of business experience. Qistina Balqis Shahrizal, Operation manager of Sugar Rush that are graduated from program Bachelor of Business Management (Hons) Operation Management and have 3 years experience in business field Sharifah Ainaa Ahmad, Financial Manager of Sugar Rush that are graduated from program Bachelor of Business Management (Hons) Finance Management and have 2 years experience in finance company. 5. Funding Needed Sugar Rush is seeking RM 50,000 to make an improvement of the production to make it more efficient which enable us to maintain our product quality so that it can compete in the market. Our ultimate goal is an exit within 4 years by way of an acquisition.